2006
DOI: 10.1038/sj.jid.5700070
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor for Advanced Glycation End Products Is Highly Expressed in the Skin and Upregulated by Advanced Glycation End Products and Tumor Necrosis Factor-Alpha

Abstract: Advanced glycation end products (AGEs) form non-enzymatically from reactions of proteins with reducing sugars. In the skin, AGEs were reported to accumulate in dermal elastin and collagens and to interact nonspecifically with the cell membrane of dermal fibroblasts. Therefore, AGEs may influence the process of skin aging. We investigated the presence of the AGE receptor RAGE in skin and the influence of AGEs on receptor expression and the formation of extracellular matrix (ECM). Sections of sun-protected and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 43 publications
7
85
0
Order By: Relevance
“…Due to the critical role of RAGE in regulating diabetes-associated chronic inflammations, most research on RAGE has been focused on diabetes-related organs and cells. Although several studies have reported RAGE expression in some epithelial cells, including eye epithelial cells (55,56), lung epithelial cells (38), and skin cells (57), so far there is no direct evidence of RAGE in the intestinal epithelium, in particular under inflammatory conditions. In this study, we demonstrated that RAGE is expressed in both cultured human intestinal epithelial cells and normal and inflammatory intestinal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the critical role of RAGE in regulating diabetes-associated chronic inflammations, most research on RAGE has been focused on diabetes-related organs and cells. Although several studies have reported RAGE expression in some epithelial cells, including eye epithelial cells (55,56), lung epithelial cells (38), and skin cells (57), so far there is no direct evidence of RAGE in the intestinal epithelium, in particular under inflammatory conditions. In this study, we demonstrated that RAGE is expressed in both cultured human intestinal epithelial cells and normal and inflammatory intestinal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AGEs induce fibroblast apoptosis by adducting to AGE receptors on the cell (Pageon, Bakala, Monnier, & Asselineau, 2007). These phenomena are also thought to be related to skin aging (Lohwasser, Neureiter, Weigle, Kirchner, & Schuppan, 2006). Therefore, in recent years, the role of AGEs has been increasingly discussed in the skin aging, and the inhibition of AGEs formation can be one of the effective strategies for direct alleviation of the development of novel antiaging cosmeceutical ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Control BSA was incubated in parallel in the absence of D-glucose. Preparation of CML-modified BSA was carried out as previously described [20] . Glycation of AGE-BSA and CML-BSA was determined using the 2,4,6-trinitrobenzenesulfonic acid (TNBS) assay [21] , resulting in a 45.6% and 36.5% glycation of lysines for AGE-BSA and CML-BSA, respectively.…”
Section: Synthesis Of Age and Cml-modified Bsamentioning
confidence: 99%